2007
DOI: 10.1111/j.1444-2906.2007.01345.x
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic changes in RNA, DNA and protein contents of laboratory-reared Pacific bluefin tuna Thunnus�orientalis

Abstract: The ontogenetic changes in the growth potential of larval and juvenile laboratoryreared Pacific bluefin tuna were examined based on RNA-DNA and protein-DNA ratios. Experimental fish were reared at the Ohshima Experiment Station of Kinki University Fisheries Laboratory in August 2002. Samples were taken from 13 to 35 days after hatching (DAH). Metamorphosis from larva to the juvenile stage was observed around 23 DAH. Somatic growth of Pacific bluefin tuna was accelerated after metamorphosis. The value of the RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 19 publications
4
29
0
1
Order By: Relevance
“…The decline of DNA concentration during development was also indicated by Buckley et al, (1999) and Fonseca et al (2006). In addition, in agreement with our results, Tanaka et al (2007) found for bluefin tuna larvae an increase in the total amount of DNA and RNA as development advanced, but the standardised RNA and protein contents per weight unit (mg/mg WW) showed steady concentrations during development. In the same study, the DNA content per unit weight began to decrease and maintained a low level from 21 DAH.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The decline of DNA concentration during development was also indicated by Buckley et al, (1999) and Fonseca et al (2006). In addition, in agreement with our results, Tanaka et al (2007) found for bluefin tuna larvae an increase in the total amount of DNA and RNA as development advanced, but the standardised RNA and protein contents per weight unit (mg/mg WW) showed steady concentrations during development. In the same study, the DNA content per unit weight began to decrease and maintained a low level from 21 DAH.…”
Section: Discussionsupporting
confidence: 80%
“…In the same study, the DNA content per unit weight began to decrease and maintained a low level from 21 DAH. At this time, the protein-DNA ratio showed a rapid increase associated with the rapid somatic growth in both length and weight, suggesting cell enlargement (Tanaka et al, 2007). Johnson and Hall (2004) also showed a decrease in hyperplasia in muscle cells in larvae larger than 20 mm in clupeid species, such as herring.…”
Section: Discussionmentioning
confidence: 94%
“…The increase after 20 DAH was due to the lower growth rate of body mass, as observed in blue fin tuna Thunnus orientalis (Temminck & Schlegel) (Tanaka et al, 2007). Based on previous observations (Park et al, 2008), the decline of protein concentration after 28 DAH was maybe due to a high rate of skeletal formation and cellular hydrolysis activity.…”
Section: Discussionmentioning
confidence: 91%
“…It was reported that white muscle of yellowfin tuna Thunnus albacores contains a considerable amount of inosinic acid among the amino acid-related compounds [34]. It was also reported that the RNA/DNA ratio in PBT drastically increases at 21 dph, suggesting that active RNA and subsequent cell proliferation take place in PBT at this stage [35]. Dietary IMP could be an important component that allows cell proliferation in PBT during the stages of fast growth.…”
Section: Discussionmentioning
confidence: 96%